Method for manufacturing electrode, electrode, and battery
Patent Information
- Application Number
- JP2023130508
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-09
AI Technical Summary
【0007】 本開示の一実施形態によれば、電子伝導性に優れる電極の製造方法、電子伝導性に優れる電極、及び電子伝導性に優れる電極を備える電池が提供される。
Smart Images

Figure 2025025610000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing an electrode, an electrode, and a battery. [Background technology]
[0002] 2. Description of the Related Art Batteries such as lithium ion secondary batteries use electrodes in which active material particles are fixed to the surface of a current collector such as a metal foil with a binder. Known methods for manufacturing electrodes include a method (also called a wet method) in which a composition made by mixing active material particles and a binder with a solvent is applied to the surface of a current collector, and a method (also called a dry method) in which active material particles are fixed to a current collector with a binder without using a solvent.
[0003] As a method for manufacturing an electrode by a dry method, a method has been proposed in which a resin that has the property of being fibrillated when a shear force is applied is used as a binder. For example, Patent Document 1 describes a method in which PTFE in a mixture containing active material particles and polytetrafluoroethylene (PTFE) is fibrillated to produce an electrode film, and then this electrode film is integrated with a current collector to manufacture an electrode. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2022-3694 A Summary of the Invention [Problem to be solved by the invention]
[0005] The electrode obtained by the method described in Patent Document 1 has high interfacial resistance at the interface between the electrode layer and the current collector, and there is room for improvement in electronic conductivity. An object of one embodiment of the present disclosure is to provide a method for producing an electrode having excellent electronic conductivity, an electrode having excellent electronic conductivity, and a battery including an electrode having excellent electronic conductivity. [Means for solving the problem]
[0006] Means for solving the above problems include the following embodiments. <1> Producing a first electrode layer disposed on a current collector; creating a second electrode layer disposed over the first electrode layer; The first electrode layer is formed by electrostatic deposition, wet deposition, or roll deposition; The second electrode layer is produced by rolling deposition, A method for producing an electrode, wherein when the first electrode layer is produced by roll-forming, at least a portion of the surface of active material particles used in the roll-forming is coated with a resin other than polytetrafluoroethylene. <2> The rolling film formation includes fiberizing polytetrafluoroethylene in a mixture containing active material particles and polytetrafluoroethylene, <1> A method for producing the electrode according to claim 1. <3> The resin different from polytetrafluoroethylene is polyvinylidene fluoride. <1> A method for producing the electrode according to claim 1. <4> a current collector, a first electrode layer disposed on the current collector, and a second electrode layer disposed on the first electrode layer; the first electrode layer includes active material particles and a resin having a polytetrafluoroethylene ratio of 0 mass% or more and less than 5 mass%, or includes active material particles at least a part of whose surface is coated with a resin different from PTFE and fibrous PTFE; The second electrode layer comprises active material particles and fibrous PTFE. <5> <4> A battery comprising the electrode according to claim 1. Effect of the Invention
[0007] According to one embodiment of the present disclosure, there are provided a method for producing an electrode with excellent electronic conductivity, an electrode with excellent electronic conductivity, and a battery including an electrode with excellent electronic conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In the present disclosure, a numerical range indicated using "~" means a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In the present disclosure, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when there are multiple substances corresponding to each component, the amount of each component means the total amount of the multiple substances, unless otherwise specified.
[0009] <Electrode manufacturing method> The method for producing an electrode according to the present disclosure includes: Producing a first electrode layer disposed on a current collector; creating a second electrode layer disposed over the first electrode layer; The first electrode layer is formed by electrostatic deposition, wet deposition, or roll deposition; The second electrode layer is produced by rolling deposition, In the method for producing an electrode, when the first electrode layer is produced by roll-forming, at least a portion of the surface of the active material particles used in the roll-forming is coated with a resin other than polytetrafluoroethylene.
[0010] The method for producing an electrode according to the present disclosure includes the steps of producing a first electrode layer disposed on a current collector, and producing a second electrode layer disposed on the first electrode layer. That is, the electrode produced by the method according to the present disclosure has a structure in which a current collector, a first electrode, and a second electrode are disposed in this order.
[0011] As shown in the examples described later, when the electrode layer disposed on the current collector is produced by roll-forming, the interface resistance at the interface between the electrode layer and the current collector tends to be high. The reason for this is thought to be that the adhesive strength of the PTFE contained as a binder in the electrode layer produced by roll-forming to the current collector is low. In the electrode manufactured by the method of the present disclosure, a first electrode is disposed between a current collector and a second electrode layer formed by roll-forming. The first electrode layer is manufactured by electrostatic film formation, wet film formation, or roll-forming, and the active material particles used in the roll-forming have at least a part of their surface coated with a resin different from PTFE. Therefore, the first electrode layer exhibits sufficient adhesive strength to the current collector. As a result, the interfacial resistance at the interface between the electrode and the current collector can be reduced, and good electronic conductivity can be achieved.
[0012] Hereinafter, the step of producing the first electrode layer will also be referred to as "step 1," and the step of producing the second electrode layer will also be referred to as "step 2."
[0013] (Process 1) In step 1, a first electrode to be placed on a current collector is prepared. The method for preparing the first electrode is electrostatic film formation, wet film formation, or roll film formation. When the method for preparing the first electrode is roll film formation, at least a part of the surface of the active material particles used for the roll film formation is coated with a resin different from PTFE.
[0014] In this disclosure, "electrostatic deposition" refers to a method in which an electrode layer material is electrostatically deposited on a current collector to form the electrode layer. In the present disclosure, the term "wet film formation" refers to a method in which a composition obtained by adding a solvent to a material for an electrode layer is applied to a current collector to form an electrode layer. In the present disclosure, "rolling film formation" refers to a method of rolling a material for an electrode layer containing PTFE to fiberize the PTFE and produce a sheet-like molded body. The electrode layer produced by rolling film formation is not formed on a current collector, but is produced as a free-standing film. The rolling process can be performed using a roll press or the like.
[0015] Among the above methods, electrostatic deposition and rolling deposition are classified as dry methods that do not use solvents. Therefore, when the first electrode layer is produced by electrostatic deposition or rolling deposition, it is advantageous in terms of reducing the manufacturing cost of the electrode and reducing the impact on the environment and living organisms.
[0016] The material used to prepare the first electrode includes, for example, active material particles and a binder, and further includes a conductive material as necessary. The type of active material particles is not particularly limited and can be selected from materials commonly used in the manufacture of electrodes. The active material particles may be positive electrode active material particles or negative electrode active material particles.
[0017] The positive electrode active material may be a lithium transition metal composite oxide. Examples of the transition metal include Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, and W. Among them, a lithium transition metal composite oxide containing at least one selected from Ni, Co, and Mn is preferable, and a lithium transition metal composite oxide (NCM, nickel cobalt manganese oxide) containing Ni, Co, and Mn is more preferable. Specific examples of lithium transition metal composite oxides include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their composite oxides (LiCo x Ni y Mn z O2, x+y+z=1), and a double oxide containing an additive element M' (LiCo a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel-type lithium manganese oxide (LiMn2O4), olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), etc. The positive electrode active material used for producing the electrode layer may be one type alone or two or more types. The volume average particle size of the positive electrode active material particles is not particularly limited and can be selected, for example, from the range of 5 μm to 30 μm.
[0018] Specific examples of the negative electrode active material include carbon materials such as graphite, soft carbon, and hard carbon, and silicon. The negative electrode active material used for producing the electrode layer may be one type alone or two or more types. The volume average particle size of the negative electrode active material particles is not particularly limited and can be selected, for example, from the range of 5 μm to 30 μm.
[0019] In the present disclosure, the volume average particle size of particles is the value (D50) at which the cumulative amount from the small diameter side reaches 50% in the volume-based particle size distribution measured by a laser diffraction / scattering method.
[0020] The type of binder is not particularly limited, and can be selected from materials commonly used in the manufacture of electrodes. When the first electrode layer is produced by electrostatic film formation or wet film formation, examples of the binder include polyvinylidene fluoride, polyethylene, polypropylene, polyethylene terephthalate, cellulose, nitrocellulose, carboxymethyl cellulose, polyethylene oxide, polyepichlorohydrin, polyacrylonitrile, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), polyacrylate, and polymethacrylate. The binder used in the preparation of the first electrode layer may be one type alone or two or more types. From the viewpoints of adhesive strength, affinity with the PTFE contained in the second electrode layer, resistance to electrolyte, etc., polyvinylidene fluoride (PVdF) is preferred as the binder. From the viewpoint of adhesion to the current collector, it is preferable that the binder does not contain PTFE or that the PTFE content is less than 5 mass %.
[0021] When the first electrode layer is formed by rolling, the binder may be PTFE. PTFE can be made into fibers by rolling to bind the active material particles and form a sheet-like molded body. PTFE may be in the form of particles. When the first electrode layer is produced by roll-forming, the binder may be PTFE alone, or a mixture of PTFE and a resin different from PTFE. When the binder is a mixture of PTFE and a resin different from PTFE when the first electrode layer is produced by roll-forming, the content of the resin different from PTFE in the mixture may be 20 parts by mass or less, 10 parts by mass or less, or 5% by mass or less relative to 100 parts by mass of PTFE.
[0022] The type of conductive material is not particularly limited, and can be selected from materials commonly used in the manufacture of electrodes. Specific examples of the conductive material include carbon materials such as carbon black (acetylene black, thermal black, furnace black, etc.), carbon nanotubes, and graphite. The conductive material used in the production of the electrode may be one type alone or two or more types.
[0023] In the material for the first electrode layer, the amount of binder per 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass. In the material for the first electrode layer, the amount of the conductive material per 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass.
[0024] When the material for the first electrode layer contains active material particles and a conductive material, a composite treatment may be carried out to fix the conductive material to the surface of the active material particles. The method for carrying out the composite treatment is not particularly limited, and can be carried out by a known method. For example, a method of applying a shear force to a mixture of active material particles and a conductive material can be mentioned. The composite treatment may be carried out in a state where the mixture of the active material particles and the conductive material contains a binder, or in a state where the mixture of the active material particles and the conductive material does not contain a binder. From the viewpoint of suppressing separation of the active material particles and the conductive material, the composite treatment is preferably carried out in a state where the mixture of the active material particles and the conductive material contains a binder.
[0025] When the first electrode layer is produced by rolling, at least a part of the surface of the active material particles used in the rolling is coated with a resin other than PTFE. The type of resin that coats the surface of the active material particles is not particularly limited and can be selected from known materials. For example, it may be selected from the binders described above. From the standpoints of adhesive strength, affinity with the PTFE contained in the first electrode layer, resistance to electrolyte, and the like, polyvinylidene fluoride (PVdF) is preferred as the resin for coating the surfaces of the active material particles. The method for coating the surfaces of the active material particles with a resin is not particularly limited, and can be carried out by any known method. For example, the surfaces of the active material particles may be coated with a binder (ie, resin) used to fix the conductive material to the surfaces of the active material particles by the above-mentioned composite treatment.
[0026] From the viewpoint of ensuring sufficient adhesion to the current collector, the coverage of the surfaces of the active material particles with the resin is preferably 3% or more, more preferably 5% or more, and even more preferably 10% or more. The coverage of the surface of the carbon particles with the resin may be 60% or less, 50% or less, or 40% or less.
[0027] The coverage of the surface of the carbon particles with the resin is measured by an image analysis method. As an image analysis method, for example, F mapping is performed by EDX (energy dispersive X-ray spectroscopy). Specifically, carbon particles covered with resin are observed by SEM (scanning electron microscope), and F mapping is performed by EDX. Regions X corresponding to the carbon particles and regions Y in region X where resin (F) exists are binarized, and the coverage is calculated by the following formula. Coverage rate (%) = (Y area / X area) x 100
[0028] There is no particular limitation on the thickness of the first electrode formed in step 1. For example, the thickness of the first electrode can be selected from the range of 10 μm to 200 μm. The material of the current collector used in step 1 is not particularly limited, and can be selected from known materials such as aluminum, copper, nickel, titanium, and stainless steel.
[0029] (Process 2) In step 2, a second electrode layer is formed on the first electrode layer. The method for forming the second electrode layer is roll-forming. The method for producing the second electrode by rolling deposition is the same as the method for producing the first electrode by rolling deposition described above. Unlike the first electrode layer, the second electrode layer is not in contact with the current collector, and therefore at least a portion of the surface of the active material particles does not need to be coated with a resin other than PTFE, as in the case where the first electrode is produced by roll-forming.
[0030] The materials used to fabricate the second electrode are similar to the materials used to fabricate the first electrode described above. In the material for the second electrode layer, the amount of binder per 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass. In the material for the second electrode layer, the amount of the conductive material per 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass.
[0031] There is no particular limitation on the thickness of the second electrode produced in step 2. For example, the thickness of the second electrode can be selected from the range of 10 μm to 200 μm.
[0032] In the method of the present disclosure, the method for integrating the electrode layer produced by roll-forming with the current collector is not particularly limited, and can be performed using a roll press, a plate press, or the like. When the first electrode layer is produced by electrostatic film formation or wet film formation, the current collector on whose surface the first electrode layer is formed is integrated with the second electrode layer. When the first electrode layer is produced by rolling deposition, the current collector, the first electrode layer, and the second electrode layer are integrated together. From the viewpoint of work efficiency, it is preferable to integrate the current collector, the first electrode layer, and the second electrode layer at the same time.
[0033] <Electrode> The electrode of the present disclosure comprises: a current collector, a first electrode layer disposed on the current collector, and a second electrode layer disposed on the first electrode layer; the first electrode layer includes active material particles and a resin having a PTFE ratio of 0 mass% or more and less than 5 mass%, or includes active material particles at least a part of whose surface is coated with a resin different from PTFE and fibrous PTFE; The second electrode layer is an electrode containing active material particles and fibrous PTFE.
[0034] In the electrode of the present disclosure, the current collector and the second electrode containing active material particles and fibrous PTFE are not in contact with each other, and a first electrode layer is disposed between them. The first electrode layer includes active material particles and a resin in which the proportion of PTFE is 0% by mass or more and less than 5% by mass, or includes active material particles at least partly coated with a resin other than PTFE and fibrous PTFE, so that the first electrode layer exhibits sufficient adhesion to the current collector. Therefore, the electrode of the present disclosure has a sufficiently low interfacial resistance at the interface between the current collector and the electrode layer, and exhibits excellent electronic conductivity.
[0035] The details and preferred aspects of the electrode and each material contained in the electrode of the present disclosure are the same as the details and preferred aspects of the electrode manufactured by the above-mentioned electrode manufacturing method and each material used therein.
[0036] In the first electrode layer, the amount of resin per 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass. When the first electrode layer contains a conductive material, the amount of the conductive material per 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass.
[0037] In the second electrode layer, the amount of PTFE per 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass. When the second electrode layer contains a conductive material, the amount of the conductive material per 100 parts by mass of the active material particles can be selected, for example, from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass.
[0038] <Battery> The battery of the present disclosure includes the electrode of the present disclosure described above. Batteries of the present disclosure include an electrode of the present disclosure as at least one of a positive electrode or a negative electrode, and in some embodiments, include an electrode of the present disclosure as a positive electrode.
[0039] The type of battery disclosed herein is not particularly limited, and can be selected from batteries such as lithium ion secondary batteries (including liquid batteries and all-solid-state batteries), lead acid batteries, nickel-metal hydride batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, cobalt titanium lithium secondary batteries, and sodium ion secondary batteries. EXAMPLES
[0040] The present disclosure will be described in more detail below with reference to examples, but the invention of the present disclosure is not limited to these examples.
[0041] <Example 1> The following materials were put into an MP mixer (Nippon Coke & Engineering Co., Ltd.) and composite treatment was carried out at 10,000 rpm for 10 minutes. When the active material particles after composite treatment were observed with an SEM, the conductive material was fixed to the surface and the surface was covered with PVdF. Active material particles: NCM (volume average particle size: 10 μm, 96.6 parts by mass) Conductive material: Acetylene black (1.5 parts by mass) Binder: PVdF (1.6 parts by mass)
[0042] Using an electrostatic screen film-forming device (Berg Kogyo Co., Ltd.), a layer containing the active material particles after the composite treatment was formed on an aluminum foil (thickness: 12 μm) as a current collector to obtain a laminate. The film-forming conditions were 1.5 kV, and the distance between the current collector and the screen was 1 cm. A load of 5 t was applied to this laminate for 1 minute using two flat plates heated to 180°C, which softened or melted the binder in the layer containing the active material particles and fixed the active material particles to the current collector, producing a first electrode layer on the current collector.
[0043] The following materials were charged into an MP mixer (Nippon Coke Engineering Co., Ltd.) and mixed at 300 rpm for 180 seconds, then further mixed at 5000 rpm for 500 seconds to form granules in which some of the PTFE particles were fibrous and the active material particles were bound by the fibrous PTFE. Active material particles: NCM (volume average particle size: 10 μm, 96.5 parts by mass) Conductive material: Acetylene black (1.5 parts by mass) Binder: PTFE (2.0 parts by mass)
[0044] The mixture containing the granules was rolled (linear pressure: 0.4 t / cm) using a roll press machine to convert the PTFE into fibers and form them into a sheet (thickness: 120 μm) to produce a second electrode layer as a self-supporting film. The obtained second electrode layer and the surface of the aluminum foil on which the first electrode layer was formed were bonded together using a roll press (linear pressure: 0.4 t / cm, 160° C.).
[0045] Through the above steps, an electrode was obtained in which the first electrode layer produced by electrostatic film formation and the second electrode layer produced by roll-forming were disposed on the current collector.
[0046] <Example 2> The following materials were put into an MP mixer (Nippon Coke & Engineering Co., Ltd.) and subjected to a composite treatment at 10,000 rpm for 10 minutes. The amounts of PVdF and PTFE were set so that the total volume was equal to the total volume of the binder used in Example 1. Active material particles: NCM (volume average particle size: 10 μm, 96.6 parts by mass) Conductive material: Acetylene black (1.5 parts by mass) Binder: PVdF (0.5 parts by mass)
[0047] After the composite treatment, PTFE (1.4 parts by mass) was further added to the MP mixer and mixed at 300 rpm for 180 seconds, followed by further mixing at 5000 rpm for 500 seconds to form granules in which the active material particles were bound by the fibrous PTFE.
[0048] The mixture containing the granules was rolled (linear pressure: 0.4 t / cm) using a roll press machine to convert the PTFE into fibers and form them into a sheet (thickness: 120 μm) to produce a first electrode layer as a self-supporting film. An aluminum foil (thickness: 12 μm) as a current collector, the first electrode layer, and a second electrode layer prepared in the same manner as the second electrode layer of Example 1 were bonded together using a roll press (linear pressure: 0.4 t / cm, 160° C.).
[0049] Through the above steps, a positive electrode was obtained in which the first electrode layer produced by electrostatic film formation and the second electrode layer produced by roll-forming film formation were disposed on the current collector.
[0050] <Comparative Example 1> An aluminum foil (thickness: 12 μm) as a current collector, a first electrode layer prepared in the same manner as the second electrode layer in Example 1, and a second electrode layer prepared in the same manner as the second electrode layer in Example 1 were bonded together using a roll press (linear pressure: 0.4 t / cm, 160° C.).
[0051] Through the above steps, a positive electrode was obtained in which the first electrode layer produced by roll-forming and the second electrode layer produced by roll-forming were disposed on the current collector.
[0052] <Evaluation of electronic conductivity> As an index of electronic conductivity of the electrodes prepared in the examples and comparative examples, the resistance at the interface between the first electrode layer and the current collector (interface resistance) was measured using an electrode resistance measurement system RM2610 (HIOKI EE Corporation). The results are shown in Table 1.
[0053] [Table 1]
[0054] As shown in Table 1, the positive electrode of Example 1 in which the first electrode layer was produced by electrostatic deposition, and the positive electrode of Example 2 in which the first electrode layer was produced by rolled deposition and the active material particles contained in the first electrode layer were coated with PVdF, have lower interfacial resistance at the interface between the first electrode layer and the current collector than the positive electrode of Comparative Example 1 in which the first electrode layer was produced by rolled deposition and the active material particles contained in the first electrode layer were not coated with PVdF. The above results are believed to be due to the fact that the first electrodes produced in Examples 1 and 2 have better adhesion to the current collector than the first electrode produced in Comparative Example 1.
Claims
1. Producing a first electrode layer disposed on a current collector; creating a second electrode layer disposed over the first electrode layer; The first electrode layer is formed by electrostatic deposition, wet deposition, or roll deposition; The second electrode layer is formed by rolling deposition, A method for producing an electrode, wherein when the first electrode layer is produced by roll-forming, at least a portion of the surface of active material particles used in the roll-forming is coated with a resin other than polytetrafluoroethylene.
2. The method for producing an electrode according to claim 1 , wherein the roll-forming step includes fiberizing polytetrafluoroethylene in a mixture containing active material particles and polytetrafluoroethylene.
3. The method for manufacturing an electrode according to claim 1 , wherein the resin different from polytetrafluoroethylene is polyvinylidene fluoride.
4. a current collector, a first electrode layer disposed on the current collector, and a second electrode layer disposed on the first electrode layer; the first electrode layer includes active material particles and a resin having a polytetrafluoroethylene ratio of 0 mass % or more and less than 5 mass %, or includes active material particles at least a part of whose surface is coated with a resin different from PTFE and fibrous PTFE; The second electrode layer comprises active material particles and fibrous PTFE.
5. A battery comprising the electrode according to claim 4.
Citation Information
Patent Citations
Positive electrode plate for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
JP2005174631A
Manufacturing method of electrode for secondary battery
JP2014049240A
Dry electrode for energy storage device and its manufacturing method
JP2017517862A
Electrode manufacturing method and electrode
JP2023073649A
Electrode, lithium battery containing them, and manufacturing method thereof
JP2023088317A